Two Layer Model for Performance Evolution of V2I Network - Bogdanovs, N.; Petersons, E.; Jansons, J. (Elektronika ir Elektrotechnika, 2013)
This research presents data evaluating data transfer rate between a remote object and base station in wireless network standard 802.1g/n. Regularity was observed in data transfer rate dependency from the M number of remote objects. All measurements and conclusions were made under circumstances where objects were positioned stationary relative to base station. As the result of the experiment, the mathematical models for two layer wireless networks and closed cyclic wireless networks were selected as ones who are to be used for choosing an optimal method for performance evaluation of a short range communication vehicular network. DOI: http://dx.doi.org/10.5755/j01.eee.19.3.3704